Hubungan Pola Asuh Orang Tua dan Sosial Kultural dengan Kejadian Diare pada Balita (0-5 Tahun) - Nuridayanti; Narmawan; Risnawati (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Diarrhea is endemic as a disease which causes death on infants. Bad child parenting and socio cultural tend to bepredisposition factor causes diarrhea. This study aims to obtain the correlation between child parenting, sociocultural, and the occurrence of diarrhea. This study aims to determine the relationship between parenting parentsand socio-cultural with the incidence of diarrhea in infants. This study is a descriptive analysis cross sectionalapproach. Sample 71 toddlers using purposive sampling technique with criteria for mothers of toddlers aged 0-5years who visited in the UPTD and were willing to become respondents. The data were obtained using a parentingquestionnaire and socio-cultural validity and reliability, the data analyzed using the chi-square test. The results ofthe analysis of the for parenting parents with the incidence of diarrhea p value =0,000 and socio-cultural with theincidence of diarrhea p value= 0,000 which means there is a relationship between parenting parents and socioculural with the incidence of diarrhea. The conclusion is that there is a significant relationship between parentingand socio-cultural parenting with the incidence of diarrhea in infants. Good parenting and culture from parents cansupport health for children under five.